DIGITAL IMAGE IN THE HIERARCHY OF CULTURAL PRACTICES: A DIALOG ABOUT THE UKRAINIAN MEDIASCAPE IN TIMES OF WAR. INTERVIEW WITH RUSLAN BORTNIK - Pavlova, Olena (Ukrainian Cultural Studies, 2023)
The topic of our conversation with political scientist, political technologist, director of the Ukrainian Institute of Politics Ruslan Bortnik is the media hierarchy in Ukraine and the modern world and the place of humanities and social sciences in information management.
Keywords: INTERVIEW